2007
DOI: 10.1523/jneurosci.3769-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced p38 Mitogen-Activated Protein Kinase Activation Mediates κ-Opioid-Dependent Dysphoria

Abstract: The molecular mechanisms mediating stress-induced dysphoria in humans and conditioned place aversion in rodents are unknown. Here, we show that repeated swim stress caused activation of both -opioid receptor (KOR) and p38 mitogen-activated protein kinase (MAPK) coexpressed in GABAergic neurons in the nucleus accumbens, cortex, and hippocampus. Sites of activation were visualized using phosphoselective antibodies against activated receptors (KOR-P) and against phospho-p38 MAPK. Surprisingly, the increase in P-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
318
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(347 citation statements)
references
References 57 publications
22
318
2
5
Order By: Relevance
“…Injection of a lentiviral-KOR construct into the DRN was sufficient to restore aversion to a KOR agonist, whereas injection of a construct encoding a mutant receptor (KOR369A) that is unable to activate p38 MAPK (24) did not restore aversive responses. This finding corroborates our report showing that p38 MAPK activation is critical for KOR-dependent CPA (25) and highlights the importance of intracellular MAPK signaling cascades in mediating mood-associated behaviors. The mechanisms by which p38 MAPK activation evokes aversive responses is unknown, however some possibilities are suggested by data Other groups have demonstrated that p38 MAPK contributes to synaptic plasticity by affecting long-term depression (37), possibly through a phosphorylation of proteins including SynGAP and AMPA receptors (38).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Injection of a lentiviral-KOR construct into the DRN was sufficient to restore aversion to a KOR agonist, whereas injection of a construct encoding a mutant receptor (KOR369A) that is unable to activate p38 MAPK (24) did not restore aversive responses. This finding corroborates our report showing that p38 MAPK activation is critical for KOR-dependent CPA (25) and highlights the importance of intracellular MAPK signaling cascades in mediating mood-associated behaviors. The mechanisms by which p38 MAPK activation evokes aversive responses is unknown, however some possibilities are suggested by data Other groups have demonstrated that p38 MAPK contributes to synaptic plasticity by affecting long-term depression (37), possibly through a phosphorylation of proteins including SynGAP and AMPA receptors (38).…”
Section: Discussionsupporting
confidence: 93%
“…3B). These results confirm that the G␣i functionality of KOR was intact (25), in concordance with reports showing that KOR-mediated ERK activation does not require GRK3 or ␤-arrestin expression (24,26).…”
Section: Viral Expression Of Kor Only In the Drn Of Kor Ko Mice Recoverssupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, their dysphoric effects require activation of the p38 MAPK pathway mediated by arrestin recruitment to the activated KOR (4, 10, 11). KOR-induced p38 MAPK activation has been demonstrated in heterologous expression systems, striatal neurons and astrocytes, spinal cord astrocytes, and in vivo (12)(13)(14) and requires KOR phosphorylation by the G protein-coupled receptor kinase 3 (GRK3) and subsequent arrestin3 recruitment (12). Based on such findings, Chavkin (11) has proposed that KOR-selective G protein-biased partial agonists that do not efficiently recruit arrestin would not cause dysphoria but would retain sufficient analgesic activity for the treatment of pain-related disorders.…”
mentioning
confidence: 99%